2013
DOI: 10.1111/mmi.12429
|View full text |Cite
|
Sign up to set email alerts
|

Lon protease inactivation, or translocation of the lon gene, potentiate bacterial evolution to antibiotic resistance

Abstract: SummaryPrevious work demonstrated that selection for Escherichia coli mutants with low antibiotic resistance frequently resulted in co-selection of lon mutations and that lon − mutants evolved higher-level resistance faster than a lon + strain. Here we show that lon mutation causes a very low multidrug resistance by inducing the AcrAB-TolC pump via stabilization of the acrAB transcriptional activators MarA and SoxS, which are substrates of the Lon protease. Fast evolution of lon − mutants towards higher resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 50 publications
3
42
0
Order By: Relevance
“…It is, therefore, possible that Lon inactivation or, alternatively, a significant down-regulation of the intracellular Lon levels, may have preceded the fixation of the triple mutant. Indeed, inactivation of Lon via insertion of the mobile element IS186 was observed previously in adaptation to other antibiotics (5,27) and in adaptation after orthologous replacement of DHFR (20). Furthermore, a dramatic drop in Lon abundance in response to chromosomal integration of destabilized DHFR mutants has been observed (24).…”
Section: Rodrigues Et Almentioning
confidence: 70%
See 1 more Smart Citation
“…It is, therefore, possible that Lon inactivation or, alternatively, a significant down-regulation of the intracellular Lon levels, may have preceded the fixation of the triple mutant. Indeed, inactivation of Lon via insertion of the mobile element IS186 was observed previously in adaptation to other antibiotics (5,27) and in adaptation after orthologous replacement of DHFR (20). Furthermore, a dramatic drop in Lon abundance in response to chromosomal integration of destabilized DHFR mutants has been observed (24).…”
Section: Rodrigues Et Almentioning
confidence: 70%
“…Inactivation or down-regulation of Lon protease, which effect is shown in Fig. 4, may constitute one such mechanism, and, in fact, has been observed recently during the evolution of strains with orthologous replacements of DHFR (20) and in the evolution of antibiotic resistance (5,27).…”
Section: Deconvolution Of Fitness Into Microlandscapes Shows Strong Ementioning
confidence: 83%
“…A previous study also revealed that lon mutants display a 40-50 % increase in acrAB transcription and high MarA levels (Nicoloff et al, 2006). Also, lon mutants confer low antibiotic resistance which is amplified by duplication of acrAB and the abundance of MarA (Nicoloff & Andersson, 2013;Nicoloff et al, 2007). However, other studies did not detect induction of marA and acrAB in lon mutants (Martin et al, 2008;White et al, 1997).…”
Section: Discussionmentioning
confidence: 95%
“…Earlier studies reported that E. coli lon mutants are sensitive to colicin (Lee et al, 2006), doxycycline (Girgis et al, 2009) and plant oils (Shapira & Mimran, 2007), but resistant to several antibiotics and organic solvents (Nicoloff & Andersson, 2013;Nicoloff et al, 2007;Watanabe & Doukyu, 2014). A previous study also revealed that lon mutants display a 40-50 % increase in acrAB transcription and high MarA levels (Nicoloff et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…In detail, deficiencies in the Lon protease result in the activation of ISs (Nicoloff et al 2007), which might lead to an elevated overall mutation rate in the genome (Chao et al 1983) and a Lon protease deficiency has explicitly been shown to facilitate sequence duplications involving the acrAB locus (Nicoloff and Andersson 2013). A similar function may be expressed by ycbZ , which shows domain homology to the Lon protease (see http://www.uniprot.org/uniprot/C4ZQ81, last accessed May 28, 2014).…”
Section: Discussionmentioning
confidence: 99%